PROPHETIC COMMUNICATION APPROACH OF FEMALE CONGREGATION THROUGH QUR’AN TEACHING AT FATHUR RAHMAN MOSQUE, SLEMAN - Hoirul Anam; Supardi; Mochamad Aris Yusuf; Shinta Nurrohmah; Nurul F. Assakinah (Universitas Islam Negeri Mataram, 2022)
Da'i is required to grasp the purpose of da'wah, this is applied to the assembly of women in the category of mothers, with their da'wah efforts to complete the blindness of the Qur'an in children who are in the Fatur Rahman Mosque environment. So, this article wants to know how the prophetic communication approach in da'wah used by female congregants. The method in this study involves qualitative research of the phenomenological type. The findings in this article reveal that women can construct an effective da'wah movement and be able to overcome the blindness of the Qur'an in children at the Fathur Rahman Mosque by adopting three da'wah strategies that are built, namely: First, motivating da'wah technique. Second, the reward da'wah approach. Third da'wah method of singing and sima'i.